CXCL2 Impairs Functions of Bone Marrow Mesenchymal Stem Cells and Can Serve as a Serum Marker in High-Fat Diet-Fed Rats - Bi, Jianhai; Li, Qiuchen; Yang, Zhigang; Cai, Lei; Lv, Tao; Yang, Xun; Yan, Li; Liu, Xia; Wang, Qian; Fu, Xin; Xiao, Ran (Frontiers in Cell and Developmental Biology, 2021)
In modern society excessive consumption of a high-fat diet (HFD) is a significant risk factor for many diseases such as diabetes, osteoarthritis and certain cancers. Resolving cellular and molecular mechanisms underlying HFD-associated disorders is of great importance to human health. Mesenchymal stem cells (MSCs) are key players in tissue homeostasis and adversely affected by prolonged HFD feeding. Low-grade systemic inflammation induced by HFD is characterized by increased levels of pro-inflammatory cytokines and alters homeostasis in many organs. However, whether, which and how HFD associated inflammatory cytokines impair MSCs remain unclear. Here we demonstrated that HFD induced serum cytokines disturbances, especially a continuous elevation of serum CXCL2 level in rats. Coincidentally, the differentially expressed genes (DEGs) of bone marrow MSCs (BMSCs) which functions were impaired in HFD rats were enriched in cytokine signaling. Further mechanism analysis revealed that CXCL2 treatment in vitro suppresses the adipogenic potential of BMSCs via Rac1 activation, and promoted BMSC migration and senescence by inducing over-production of ELMO1 and reactive oxygen species (ROS) respectively. Moreover, we found that although glycolipid metabolism indicators can be corrected, the CXCL2 elevation and BMSC dysfunctions cannot be fully rescued by diet correction and anti-inflammatory aspirin treatment, indicating the long-lasting deleterious effects of HFD on serum CXCL2 levels and BMSC functions. Altogether, our findings identify CXCL2 as an important regulator in BMSCs functions and may serve as a serum marker to indicate the BMSC dysfunctions induced by HFD. In addition, our findings underscore the intricate link among high-fat intake, chronic inflammation and BMSC dysfunction which may facilitate development of protective strategies for HFD associated diseases.